Aplicação dos parâmetros fundamentais de autonomia e controle do regime regulatório brasileiro no desenho institucional das agências reguladoras estaduais - Gil, Thiago Barbosa (2019)
This dissertation aims to identify historical processes that led to the definition of the institutional design initially developed for the Brazilian federal regulatory agencies of infrastructure, specifically for their control and autonomy, vis-à-vis the dynamic that creates the regulatory regime in the States of Brazil. The research initially focuses on the concrete investigation of the dimensions of the concepts of autonomy and control, which are the parameters for the process of creation and implementation of the Brazilian regulatory agencies. After establishing the historical conceptual frameworks of autonomy and control, the objective will be to expand the analysis for the institutional designs of autonomy and control of the state-level regulatory agencies. In other words, the desire is to find the parameters of what was defined in Brazil as autonomy and control of independent regulatory agencies and then operationalize the indicators of these concepts in the empirical section. From the orientation provided by the operationalization, it is desired to describe the dimensions of autonomy and control of the state agencies and their empirical classification.